Line 14: Line 14:
  
 
We often do not work with the random variable we observe directly, but with some function of that random variable. So, instead of working with a random variable X, we might instead have some random variable Y=g(X) for some function g:'''R''' → '''R'''.<br/>
 
We often do not work with the random variable we observe directly, but with some function of that random variable. So, instead of working with a random variable X, we might instead have some random variable Y=g(X) for some function g:'''R''' → '''R'''.<br/>
In this case, we might model Y directly to bet f<math>_Y</math>(y), especially if we do not know g. Or we might have a model for X and find f<math>_Y</math>(y) (or p<math>_Y</math>(y)) as a function of f<math>_X</math> (or p<math>_X</math> and g. <br/>
+
In this case, we might model Y directly to get f<math>_Y</math>(y), especially if we do not know g. Or we might have a model for X and find f<math>_Y</math>(y) (or p<math>_Y</math>(y)) as a function of f<math>_X</math> (or p<math>_X</math> and g. <br/>
 
We will discuss the latter approach here.
 
We will discuss the latter approach here.
  
Line 40: Line 40:
 
==Case 1: X and Y Discrete ==
 
==Case 1: X and Y Discrete ==
  
Let <math>R_X</math> ≡ X(''S'') be the range space of X and <math>R_Y</math> ≡ g(X(''S'')) be the range space of Y. Then the pmf of Y is <br/>
+
Let <math>R_X</math> ≡ X(''S'') be the range space of X and <math>R_Y</math> ≡ g(X(''S'')) be the range space of Y (i.e. the image of X(''S'') under g). Then the pmf of Y is <br/>
 
<center>p<math>_Y</math>(y) = P(Y=y) = P(g(X)=y)</center>
 
<center>p<math>_Y</math>(y) = P(Y=y) = P(g(X)=y)</center>
 
But this means that <br/>
 
But this means that <br/>
Line 66: Line 66:
  
 
The pmf of Y in this case is <br/>
 
The pmf of Y in this case is <br/>
<center>p<math>_Y</math>(y) = P(g(X)=y) = P(X ∈ D<math>_Y</math>) =</center><br/>
+
<center>p<math>_Y</math>(y) = P(g(X)=y) = P(X ∈ D<math>_y</math>)</center><br/>
<center>where D<math>_Y</math> ≡ {x ∈ '''R''': g(x)=y} ∀y ∈ ''R''<math>_Y</math></center>
+
<center>where D<math>_y</math> ≡ {x ∈ '''R''': g(x)=y} ∀y ∈ ''R''<math>_y</math></center>
 +
i.e. for a given y ∈ ''R''<math>_y</math>, D<math>_y</math> is the set of all x ∈ '''R''' such that g(x) = y.
  
 
Then, <br/>
 
Then, <br/>
<center><math> p_Y(y) = \int_{D_y}f)X(x)dx</math></center>
+
<center><math> p_Y(y) = \int_{D_y}f_X(x)dx</math></center>
  
 
'''Example''' Let g(x) = u(x - x<math>_0</math>) for some x<math>_0</math> ∈ '''R''', and let Y=g(X). Then <math>R_Y</math> = {0,1} and <br/>
 
'''Example''' Let g(x) = u(x - x<math>_0</math>) for some x<math>_0</math> ∈ '''R''', and let Y=g(X). Then <math>R_Y</math> = {0,1} and <br/>
Line 93: Line 94:
 
<center>F<math>_Y</math>(y) = P(g(X) ≤ y) = P(X ∈ D<math>_y</math>) <br/>
 
<center>F<math>_Y</math>(y) = P(g(X) ≤ y) = P(X ∈ D<math>_y</math>) <br/>
 
where D<math>_y</math> = {x ∈ '''R''': g(x) ≤ y}.</center>
 
where D<math>_y</math> = {x ∈ '''R''': g(x) ≤ y}.</center>
 +
i.e. for a given y ∈ '''R''', D<math>_y</math> is the set of all x ∈ '''R''' such that g(x) ≤ y.
 +
 
Then <br/>
 
Then <br/>
 
<center><math>F_Y(f) = \int_{D_y}f_X(x)dx</math></center>
 
<center><math>F_Y(f) = \int_{D_y}f_X(x)dx</math></center>
Line 150: Line 153:
 
and <br/>
 
and <br/>
 
<center><math>F_Y(y) = \int_{-\sqrt{y}}^{\sqrt{y}}f_X(x)dx</math></center>
 
<center><math>F_Y(y) = \int_{-\sqrt{y}}^{\sqrt{y}}f_X(x)dx</math></center>
 +
 +
For general y, we need to find subsets of the y-axis that have solutions of the same form and solve the problems separately for the different subsets.
  
  
Line 158: Line 163:
  
 
'''Proof:'''<br/>
 
'''Proof:'''<br/>
First consider g monotone (strictly monotone) increasing
+
First consider g monotone (strictly monotone) increasing (note that for differentiable and hence continuous functions defined for a given interval, injective implies monotonicity)
  
 
<center>[[Image:fig4_functions_on_rv.png|400px|thumb|left|Fig 4: Function g is strictly increasing on its domain.]]</center>
 
<center>[[Image:fig4_functions_on_rv.png|400px|thumb|left|Fig 4: Function g is strictly increasing on its domain.]]</center>

Revision as of 15:11, 10 November 2013


Random Variables and Signals

Topic 8: Functions of Random Variables




We often do not work with the random variable we observe directly, but with some function of that random variable. So, instead of working with a random variable X, we might instead have some random variable Y=g(X) for some function g:RR.
In this case, we might model Y directly to get f$ _Y $(y), especially if we do not know g. Or we might have a model for X and find f$ _Y $(y) (or p$ _Y $(y)) as a function of f$ _X $ (or p$ _X $ and g.
We will discuss the latter approach here.

More formally, let X be a random variable on (S,F,P) and consider a mapping g:RR. Then let Y$ (\omega)= $g(X($ \omega)) $$ \omega $S.
We normally write this as Y=g(X).

Graphically,

Fig 1: Mapping from S to X to Y under g


Is Y a random variable? We must have Y$ ^{-1} $(A) ≡ {$ \omega $S: Y$ (\omega) $ ∈ A} = {$ \omega $S: g(X$ (\omega) $) ∈ A} be an element of F ∀A ∈ B(R) (Y must be Borel measurable).
We will only consider functions g in this class for which Y$ ^{-1} $(A) ∈ F ∀A ∈ B(R), so that if Y=g(X) for some random variable X, Y will be a random variable.

What is the distribution of Y? Consider 3 cases:

  1. X discrete, Y discrete
  2. X continuous, Y discrete
  3. X continuous, Y continuous

Note: you cannot have a continuous Y from a discrete X.



Case 1: X and Y Discrete

Let $ R_X $ ≡ X(S) be the range space of X and $ R_Y $ ≡ g(X(S)) be the range space of Y (i.e. the image of X(S) under g). Then the pmf of Y is

p$ _Y $(y) = P(Y=y) = P(g(X)=y)

But this means that

$ p_Y(y) = \sum_{x\in\mathcal{R}_X:g(x)=y}p_X(x)\;\;\forall y\in\mathcal{R}_Y $


Example $ \quad $ Let X be the value rolled on a die and

$ Y = \begin{cases} 1 & \mbox{if}\;X\;\mbox{is odd} \\ 0 & \mbox{if}\;X\;\mbox{is even} \end{cases} $

Then R$ _X $ = {0,1,2,3,4,5,6} and R$ _Y $ = {0,1} and g(x) = x % 2.

Now
$ p_Y(y) = \sum_{x\in\mathcal{R}_X:g(x)=y}p_X(x) $
$ \begin{align} \Rightarrow p_Y(0) &= p_X(2)+p_X(4)+p_X(6) \\ p_Y(1) &= p_X(1)+p_X(3)+p_X(5) \end{align} $



Case 2: X Continuous, Y Discrete

The pmf of Y in this case is

p$ _Y $(y) = P(g(X)=y) = P(X ∈ D$ _y $)

where D$ _y $ ≡ {x ∈ R: g(x)=y} ∀y ∈ R$ _y $

i.e. for a given y ∈ R$ _y $, D$ _y $ is the set of all x ∈ R such that g(x) = y.

Then,

$ p_Y(y) = \int_{D_y}f_X(x)dx $

Example Let g(x) = u(x - x$ _0 $) for some x$ _0 $R, and let Y=g(X). Then $ R_Y $ = {0,1} and

D$ _0 $ = {x ∈ R: x < x$ _0 $} = (-∞, x$ _0 $)
D$ _1 $ = {x ∈ R: x ≥ x$ _0 $} = [ x$ _0 $, ∞)

So,

$ p_Y(y) = \begin{cases} \int_{-\infty}^{x_0} f_X(x)dx & y=0\\ \\ \int_{x_0}^{-\infty} f_X(x)dx & y=1 \end{cases} $



Case 3: X and Y Continuous

We will discuss 2 methods for finding f$ _Y $ in this case.

Approach 1
First, find the cdf F$ _Y $.

F$ _Y $(y) = P(g(X) ≤ y) = P(X ∈ D$ _y $)
where D$ _y $ = {x ∈ R: g(x) ≤ y}.

i.e. for a given y ∈ R, D$ _y $ is the set of all x ∈ R such that g(x) ≤ y.

Then

$ F_Y(f) = \int_{D_y}f_X(x)dx $

Differentiate F$ _Y $ to get f$ _y $.

You can find D$ _Y $ graphically or analytically


Example

Fig 2: This plot of g(x) can be used to derive D$ _Y $ graphically


For y = y$ _1 $ and y = y$ _2 $,

$ \begin{align} D_{y_1} &= \{x:\;x \leq x_1\} \\ D_{y_2} &= \{x:\;x\leq x_2'\} \cup \{x:\;x_2''<x\leq x_2'''\} \end{align} $

Then

$ \begin{align} F_Y(y_1) &= \int_{-\infty}^{x_1}f_X(x)dx \\ \\ F_Y(y_2) &= \int_{-\infty}^{x_2'}f_X(x)dx + \int_{x_2''}^{x_2'''}f_X(x)dx \end{align} $


Example Y = aX + b, a,b ∈ R, a ≠ 0

F$ _Y $(y) = P(aX + b ≤ y)

So,

$ \begin{align} D_y&=\{x\in\mathbb R: x\leq\frac{y-b}{a}\}\quad\mbox{if}\;a>0 \\ D_y&=\{x\in\mathbb R: x\geq\frac{y-b}{a}\}\quad\mbox{if}\;a<0 \end{align} $

Then

$ F_Y(y)=\begin{cases} \int_{-\infty}^{\frac{y-b}{a}}f_X(x)dx & \mbox{if }\;a>0 \\ \\ \int_{\frac{y-b}{a}}^{-\infty}f_X(x)dx & \mbox{if }\;a<0 \end{cases} $


Example Y = X$ ^2 $

Fig 3: Y = X$ ^2 $


For y < 0, D$ _y $ = ø
For y ≥ 0,

$ \begin{align} F_Y(y) &= P(X^2\leq y) \\ &= P(-\sqrt{y} <X\leq \sqrt{y}) \end{align} $

So,

$ D_y = (-\sqrt{y},\sqrt{y}) $

and

$ F_Y(y) = \int_{-\sqrt{y}}^{\sqrt{y}}f_X(x)dx $

For general y, we need to find subsets of the y-axis that have solutions of the same form and solve the problems separately for the different subsets.


Approach 2

Use a formula for f$ _y $ in terms of f$ _X $. To derive the formula, assume the inverse function g$ ^{-1} $ exists, so if y = g(x), then x = g$ ^{-1} $(y). Also assume g and g$ ^{-1} $ are differentiable. Then, if Y = g(X), we have that

$ f_Y(y) = \frac{f_X(g^{-1}(y))}{|\frac{dy}{dx}|_{x=g^{-1}(y)}} $

Proof:
First consider g monotone (strictly monotone) increasing (note that for differentiable and hence continuous functions defined for a given interval, injective implies monotonicity)

Fig 4: Function g is strictly increasing on its domain.


Since {y < Y ≤ y + Δy} = {x < X ≤ x + Δx}, we have that P(y < Y ≤ y + Δy) = P(x < X ≤ x + Δx).

Use the following approximations:

  • P(y < Y ≤ y + Δy) ≈ f$ _Y $(y)Δy
  • P(x < X ≤ x + Δx) ≈ f$ _X $(x)Δx
Fig 5: P(y < Y ≤ y + Δy) ≈ f$ _Y $(y)Δy


Since the left hand sides are equal,

$ f_Y(y)\Delta y \approx f_X(x)\Delta x $

Now as Δy → 0, we also have that Δx → 0 since g is continuous, and the approximations above become equalities. We rename Δy, Δx as dy and dx respectively, so letting Δy → 0, we get

$ \begin{align} f_Y(y)dy &= f_X(x)dx \\ \Rightarrow f_Y(y)&=f_X(x)\frac{dx}{dy} \end{align} $


We normally write this as

$ f_Y(y) = \frac{f_X(g^{-1}(y))}{\frac{dy}{dx}|_{x=g^{-1}(y)}} $

A similar derivation for g monotone decreasing gives us the general result for invertible g:

$ f_Y(y) = \frac{f_X(g^{-1}(y))}{|\frac{dy}{dx}|_{x=g^{-1}(y)}} $

Note this result can be extended to the case where y = g(x) has n solutions x$ _1 $,...,x$ _n $, in which case,

$ f(Y(y) = \sum_{i=1}^n\frac{f_X(x_n)}{|\frac{dy}{dx}|_{x=x_n}} $

For example, if Y = X$ ^2 $,

$ x_1 = -\sqrt{y},\;\;x_2 = \sqrt{y} $
$ \Rightarrow f_Y(y) = \frac{f_X(-\sqrt{y})}{2\sqrt{y}}+\frac{f_X(\sqrt{y})}{2\sqrt{y}} $



References



Questions and comments

If you have any questions, comments, etc. please post them on this page



Back to all ECE 600 notes

Alumni Liaison

Followed her dream after having raised her family.

Ruth Enoch, PhD Mathematics